Endothelin Receptors Expressed by Immune Cells Are Involved in Modulation of Inflammation and in Fibrosis: Relevance to the Pathogenesis of Systemic Sclerosis - Tinazzi Elisa; Puccetti Antonio; Patuzzo Giuseppe; Barbieri Alessandro; Argentino Giuseppe; Confente Federico; Dolcino Marzia; Beri Ruggero; Marchi Giacomo; Ottria Andrea; Righetti Daniela; Rampudda Mariaelisa; et al. (Journal of Immunology Research)
Endothelin-1 (ET-1) plays a pivotal role in vasoconstriction, fibrosis, and inflammation, the key features of systemic sclerosis (SSc). ET-1 receptors (ETA and ETB) are expressed on endothelial cells, smooth muscle cells, and fibroblasts, but their presence on immune cells has not been deeply investigated so far. Endothelin receptors antagonists such as bosentan have beneficial effects on vasoconstriction and fibrosis, but less is known about their potential anti-inflammatory effects. We studied the expression of ET-1 receptors on immune cells (T and B lymphocytes, monocytes, and neutrophils) and the link between ET-1 and inflammation in patients with SSc. We show here that ET-1 exerts a proinflammatory effect in CD4+ T cells, since it induces an increased IFN-γ production; preincubation with antagonists of both receptors reduces IFN-γ production. Moreover, following ET-1 stimulation, neutrophils produce proinflammatory mediators, thus amplifying the effects of activated CD4+ T cells. Our data indicate that ET-1 system is involved in the pathogenesis of inflammation and fibrosis typical of SSc, through the activation of T lymphocytes and neutrophils and the consequent release of proinflammatory and profibrotic cytokines. These findings suggest that dual ET-1 receptors antagonist therapy, besides its effect on vasculopathy, has a profound impact on the immune system favouring antiinflammatory and antifibrogenic effects.